Categorical Determinations and Conceptual Notion of Education: A Critical Reading in Terms of the Interregional Indo-European System - Herra Castro, Ernesto (2017)
This article tries to identify different educational moments subsumed in scientific knowledge as one of the many manifestations of human knowledge with the purpose of boosting other kind of horizons of sense to encourage the production and reproduction of community life. It identifies the contributions of Indo-European knowledge and the existing tensions from the formalization of knowledge by Greek rationality.